Alternative Ways to Resolve Disputes Related to Consumer Protection of Financial Services in Hong Kong, Singapore and the United States: Innovations 2017 – 2019 - IVANOVSKAYA, Natalia V.; ISAI, Sergey S. (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The authors explore regulatory innovations in financial services consumer protection in Hong Kong, Singapore, and the United States. It was revealed that: (1) the priority of such an alternative way of regulating financial demand with the participation of consumers as mediation is ensured by the activities of the FDRC Center in Hong Kong, and in Singapore – by the new law on mediation in 2017; (2) the creation of a unified mediation model, which is mandatory for all member states – the Singapore Convention on Mediation 2019 – will allow mediation to become the most widely used alternative way to resolve cross-border, including financial, disputes; (3) a positive result of the application of arbitration in the field of settlement of financial disputes with the participation of large banks can be achieved by creating certain conditions, including by attracting highly professional arbitrators with extensive practical experience, as, for example, was done by the Hong Kong International Arbitration Center (HKIAC); (4) on the example of the US experience, one can also identify another way to improve the mechanisms for resolving financial disputes, the goals and objectives of which are shifted from the vector of propaganda and updating alternative methods of resolving financial disputes to improving the mechanism for providing financial services; (5) the inclusion of a clause on the mandatory resolution of possible disputes in arbitration, as a mandatory part of the contract itself with consumers, indicates the deprivation of the right to choose the method of resolving the dispute by the consumer, and also deprives them of the right to file collective claims.